The global, regional, and national early-onset colorectal cancer burden and trends from 1990 to 2019: results from the Global Burden of Disease Study 2019 - Hongfeng Pan; Zeyi Zhao; Yu Deng; Zhifang Zheng; Ying Huang; Shenghui Huang; Pan Chi (BMC, 2022)
Abstract Purpose The incidence of early-onset colorectal cancer (EO-CRC), which occurs in people under age 50, has been increasing annually. The aim of this study was to provide an up-to-date estimate of the global EO-CRC burden. Methods We used Global Burden of Disease Study data and methodologies to describe changes in the EO-CRC burden from 1990 to 2019, including incidence, prevalence, mortality, and disability-adjusted life years (DALYs). The driving factors for cancer burden variation were further analyzed using decomposition analysis. Frontier analysis was used to visually demonstrate the potential for burden reduction in each country or region based on their development levels. Results The global EO-CRC incidence more than doubled, increasing from 95,737 (95% uncertainty interval (UI): 90,838-101.042) /100,000 in 1990 to 226,782 (95% UI: 207,495-248,604) /100,000 in 2019. Additionally, related deaths increased from 50,997 (95% UI: 47,692-54,410) /100,000 to 87,014 (95% UI: 80,259-94,339) /100,000, and DALYs increased from 256,1842 (95% UI: 239,4962-2,735,823) /100,000 to 4,297,573 (95% UI: 3,965,485-4,650,790) /100,000. Regarding age-standardized rates, incidence and prevalence increased significantly, while mortality and DALYs rate were basically unchanged. Decomposition analysis showed a significant increase in DALYs in the middle sociodemographic index (SDI) quintile region, in which aging and population growth played a major driving role. Frontier analysis showed that countries or regions with a higher SDI quintile tend to have greater improvement potential. Conclusion The current EO-CRC burden was found to be the greatest in the high-middle SDI quintile region and East Asia, which may need to adjust screening guidelines accordingly and introduce more effective interventions.